Review of Development and Application of Main Micro-hydraulic Components and Key Technologies - Jianying, Li; Guodong, Qu; Shuai, Xie; Chen, Peng (Recent Patents on Engineering, 2025)
Micro-hydraulic components and key technologies are important directions of fluid transmission and control, which are widely used in the national defense industry, production line conveying equipment, exoskeleton robot, and more.The current development status of miniature hydraulic components and key technologies is summarized, and the existing advantages of hydraulic components and technology are pointed out, and the research object is focused on relevant papers and patents.We study the beneficial effects of the existing microcomponents and technologies, the performance indexes of typical products, and the latest progress in their structure innovation, material replacement, testing methods, and processing technology are summarized.Typical achievements, core components, and manufacturing aspects are studied in-depth. They become smaller with increased output power and find more diverse scenarios with advancing technology maturity.By improving the hardware structure of the existing miniature hydraulic component, and constantly innovating the processing technology, miniature hydraulic components will improve their efficiency and power density and will focus on further miniaturization in the future.
Keywords: high pressure